Pengembangan UMKM “Rengginang” di Desa Karangmekar - Andi Suhandi; Azmy MH; Bayu Umara; Bernad Hananto; Saphira VJ (LPPM STEBIS YPII, 2024)
Community service activities aim to help empower various potentials in the environment around the Village and also its community. One of the targets in this Community Service Activity is the empowerment of MSMEs. Empowerment of MSMEs is one of the focuses in increasing income, expanding market share, and legalizing the form of MSME businesses. After implementing the Community Service programs, the results showed that the implementation of programs related to the empowerment of MSMEs, especially in Mr. Warsa's business, showed positive results. Where Mr. Warsa's business now has legalization with the possession of a NIB. As well as the creation of a business logo, packaging label, and business banner has a good impact on the marketing process with the increasing recognition of Mr. Warsa's business. Which in this case can certainly expand the market share, and increase income.